2022
DOI: 10.1007/s00125-022-05694-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dapagliflozin on kidney and cardiovascular outcomes by baseline KDIGO risk categories: a post hoc analysis of the DAPA-CKD trial

Abstract: Aims/hypothesis In the Dapagliflozin and Prevention of Adverse Outcomes in Chronic Kidney Disease (DAPA-CKD) trial, dapagliflozin reduced the risks of progressive kidney disease, hospitalised heart failure or cardiovascular death, and death from all causes in patients with chronic kidney disease (CKD) with or without type 2 diabetes. Patients with more severe CKD are at higher risk of kidney failure, cardiovascular events and all-cause mortality. In this post hoc analysis, we assessed the efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 27 publications
3
17
0
10
Order By: Relevance
“…The results of our analysis indicated that, compared to placebo, SGLT-2 inhibitors could reduce the overall cardiorenal risk by 29%, the risk of kidney disease progression by 31%, and the risk of CV death or hospitalization for HF by 25%. Similar bene ts were found in patients coexisting CKD and T2DM, which was consistent with the results of previous studies conducted on T2DM populations [35][36][37][38]. In addition, our results also suggested that the cardiorenal bene ts of SGLT-2 inhibitors were similar in CKD patients with eGFR 45 mL/min/1.73 m 2 and those with better eGFR levels, although the relative risk reduction was numerically higher in individuals with eGFR ≥ 45 mL/min/1.73 m 2 (38% vs 24%).…”
Section: Discussionsupporting
confidence: 92%
“…The results of our analysis indicated that, compared to placebo, SGLT-2 inhibitors could reduce the overall cardiorenal risk by 29%, the risk of kidney disease progression by 31%, and the risk of CV death or hospitalization for HF by 25%. Similar bene ts were found in patients coexisting CKD and T2DM, which was consistent with the results of previous studies conducted on T2DM populations [35][36][37][38]. In addition, our results also suggested that the cardiorenal bene ts of SGLT-2 inhibitors were similar in CKD patients with eGFR 45 mL/min/1.73 m 2 and those with better eGFR levels, although the relative risk reduction was numerically higher in individuals with eGFR ≥ 45 mL/min/1.73 m 2 (38% vs 24%).…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, the significant renal benefits observed in the smallest eGFR categories show that SGLT2is protect the kidney also through other pathways, which may include enhancement of kidney oxygenation, direct effects on glomerular endothelial function, metabolic and anti‐inflammatory effects 44 . Furthermore, a recent post hoc analysis of the DAPA‐CKD trial, which evaluated the effect of dapagliflozin on a composite renal outcome in subjects with and without T2D with an eGFR of between 25 and 75 ml/min/1.73m 2 and urine albumin‐to creatinine ratio (UACR) of between 20 and 5000 mg/g, showed more pronounced benefits among participants with higher UACR, also suggesting albuminuria‐lowering effects 40 . Conversely, although the fundamental mechanisms responsible for the beneficial cardiac effects of SGLT2is have yet not been clarified, the observed trend towards higher HF benefits with declining eGFR suggests that the pathways through which SGLT2is exert their cardioprotective effects are kidney‐independent and support the existence of different mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…Основываясь на том, что у лиц с более выраженными стадиями ХБП выше риск развития терминальной стадии болезни почек, сердечно-сосудистых событий и смертности, S. Waijer и соавт. выполнили post-hoc-анализ результатов исследования DAPA-CKD с целью оценки эффективности и безопасности дапаглифлозина в зависимости от исходной категории риска по широко используемой классификации KDIGO [21]. Более высокий уровень альбуминурии и более низкий показатель рСКФ являются предикторами почечной недостаточности и сердечно-сосудис тых событий и включены в классификационную систему KDIGO по оценке комбинированного сердечно-сосудистого и почечного риска [22].…”
Section: эффекты дапаглифлозина на сердечнососудистые и ренальные исх...unclassified
“…Для этого исследователи разделили пациентов на подгруппы, взяв за основу категории комбинированного риска сердечно-сосудистых и почечных событий у пациентов с ХБП в зависимости от категории рСКФ и альбуминурии KDIGO, проведя, однако, их определенную модификацию [21,22]. Необходимость модификации была обусловлена тем, что исходно абсолютное большинство участников исследования DAPA-CKD относились к категории очень высокого риска по KDIGO, в связи с этим создание дополнительной категории «умеренно-высокого риска» позволило сформировать когорты с относительно сопоставимыми размерами для дальнейшей стратификации.…”
Section: эффекты дапаглифлозина на сердечнососудистые и ренальные исх...unclassified